MOTIVASI PETERNAK PLASMA AYAM BROILER DALAM BERMITRADI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (Studi Kasus PT. Pelita Trikencana Bersinar) - Ady Santoso; Cepriadi '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is knowing motivation of broiler breeders in partnering and problems in partnership with PT. Pelita Trikencana Bersinar in Kampar Kiri Tengah District, Kampar Regency. Type of research is a descriptive study using quantitative data and qualitative. Data collection was done through interviews with the help of questionnaires. The data analysis used is descriptive statistics analysis tool factors. Descriptive analysis results indicate a partnership is a partnership that is run plasma core system, with the system and partner acceptance procedures are clearly specified in the letter of agreement. In addition, the contract price of feed, DOC, and live shicken price agreed in the contract signed by each production period. The result of factor analysis showed 7 variables qualify resulting in 2 motivation formations. Motivation formation named the main motivation and motivational support. Motivation that encourages breeders in partnership is the main motivation consists of variable control (X2), working conditions (X5), achievement (X6), employment (X8), and material needs (X9). The main motivation have real influence is the motivation broiler breeders in prtnering. While supporting motivation consists of variable interpersonal relationships (X3), and compensation (X4). Motivational support has a role that is lower than the primary motivation. The results of descriptive analysis shows that the dominant problems occur is unilateral cooperation contract, the contract price is the determined unilaterlly sapronak and production, lack of clear quality standars sapronak sent the core, late harvest, the absence of an arbitration body, and the absence of institutional support. Key word : Broiler, Motivation of breeder, Parthership